The Way We Learn Our Names Is Written in the Sky: Personification in the Capitalocene - MacDonald, Michael B. (Farol, 2024)
The summer sky now often turns the color of turmeric. Smoke from wildfires, blown in from hundreds of miles away, is trapped like huge nets between buildings. Edmonton, Alberta, where I have lived for almost twenty years, is a city on the edge of the Canadian Boreal Forest. This forest is part of the Taiga, the second largest forest in the world, which stretches across Canada and continues into Iceland, Norway, Sweden, Finland, Russia, Mongolia, and Japan. In Canada, it covers 270 million hectares of flat plains and treeless Arctic tundra. The Boreal Forest is home to more than 600 indigenous communities, is home to most of Canada’s known fossil fuel reserves, stores more than 208 billion tons of carbon (11 percent of the world’s total), and, together with the Amazon Rainforest, constitutes one of the two great lungs of the planet.